(untitled) (Texas Journal of Medical Science, 2023)
The purpose of the study is to study the prevalence of hypothyroidism among the population, its course, to study the frequency of occurrence of hypothyroidism, prognosis, prevention and the impact of the thyroid gland on the functioning of other systems and organs. Diagnosis of hypothyroidism is based on an assessment of the clinical picture and data from laboratory and instrumental research methods. Laboratory testing of serum TSH and thyroid hormone levels is fundamental in diagnosing decreased thyroid function. The main role is given to the determination of thyriotropic hormone by highly sensitive methods